2023
DOI: 10.21203/rs.3.rs-3488308/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Choline Alphoscerate for Amnestic Mild Cognitive Impairment: A Randomized Double-Blind Placebo-Controlled Trial

Jong-Wook Jeon,
Su-Young Lee,
Seung Hoon Lee
et al.

Abstract: Background Effective interventions for overall healthy subjects with mild cognitive impairment are currently limited. Choline alphoscerate (alpha glyceryl phosphorylcholine, αGPC) is a choline-containing phospholipid used to treat cognitive function impairments in specific neurological conditions. This study aimed to investigate the efficacy and safety of αGPC in individuals diagnosed with mild cognitive impairment. Methods In this multicenter, randomized, placebo-controlled trial, 100 study subjects with mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Choline alphoscerate (alpha glyceryl phosphorylcholine, α-GPC), a cognition-enhancing choline-containing phospholipid, is explored for countering cognitive impairment in conditions like AD and stroke ( Tayebati, Di Tullio, Tomassoni and Amenta, 2009 ). Recognized as a parasympathetic agent, α-GPC, used as a registered drug or nutraceutical ( Parker et al, 2022 ), has demonstrated in preclinical studies to increase acetylcholine release ( Wang et al, 2009 ), improve learning and memory, and is under evaluation in clinical trials for efficacy and Safety in VCID Patients (NCT05050604) ( Salvadori et al, 2021 ; Jeon et al, 2023 ). Choline-containing phospholipids emerge as an unexplored category of drugs in the context of PSD and reactive astrogliosis.…”
Section: Therapeutic Strategies To Attenuate Reactive Astrogliosis An...mentioning
confidence: 99%
“…Choline alphoscerate (alpha glyceryl phosphorylcholine, α-GPC), a cognition-enhancing choline-containing phospholipid, is explored for countering cognitive impairment in conditions like AD and stroke ( Tayebati, Di Tullio, Tomassoni and Amenta, 2009 ). Recognized as a parasympathetic agent, α-GPC, used as a registered drug or nutraceutical ( Parker et al, 2022 ), has demonstrated in preclinical studies to increase acetylcholine release ( Wang et al, 2009 ), improve learning and memory, and is under evaluation in clinical trials for efficacy and Safety in VCID Patients (NCT05050604) ( Salvadori et al, 2021 ; Jeon et al, 2023 ). Choline-containing phospholipids emerge as an unexplored category of drugs in the context of PSD and reactive astrogliosis.…”
Section: Therapeutic Strategies To Attenuate Reactive Astrogliosis An...mentioning
confidence: 99%